Willow Brook Road [large type] - Woods, Sherryl (Woods, Sherryl. Chesapeake Shores novel., 2016)
"Carrie Winters has come home from Europe, glamorous fashion career behind her and her heart broken and finds herself drawn to grief-stricken Sam Winslow who is raising his nephew after the boy's parents were killed in an accident two weeks ago"--